2014
DOI: 10.1155/2014/639896
|View full text |Cite
|
Sign up to set email alerts
|

The c-MYC Protooncogene Expression in Cholesteatoma

Abstract: Cholesteatoma is an epidermoid cyst, which is most frequently found in the middle ear. The matrix of cholesteatoma is histologically similar to the matrix of the epidermoid cyst of the skin (atheroma); their epithelium is characterized by hyperproliferation. The c-MYC protooncogene located on chromosome 8q24 encodes a transcription factor involved in the regulation of cell proliferation and differentiation. Previous studies have found aneuploidy of chromosome 8, copy number variation of c-MYC gene, and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Meanwhile, MiR-125b was shown to be down-regulated in psoriasis and cutaneous squamous cell carcinoma, and its overexpression can suppresses the proliferation of keratinocytes [9][10][11]. Cholesteatoma has the same abnormal proliferation characteristics as malignancies, which has been confirmed by many studies which found that many tumour-related genes and proliferation markers had abnormally high expression in cholesteatoma [26,27]. Similar to psoriasis, cholesteatoma has aberrant proliferation of keratinocytes in an environment full of inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…Meanwhile, MiR-125b was shown to be down-regulated in psoriasis and cutaneous squamous cell carcinoma, and its overexpression can suppresses the proliferation of keratinocytes [9][10][11]. Cholesteatoma has the same abnormal proliferation characteristics as malignancies, which has been confirmed by many studies which found that many tumour-related genes and proliferation markers had abnormally high expression in cholesteatoma [26,27]. Similar to psoriasis, cholesteatoma has aberrant proliferation of keratinocytes in an environment full of inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, the proto‐oncogenes c‐myc and c‐jun have been strongly linked to keratinocyte differentiation and proliferation in cholesteatomas . The c‐myc gene is located on chromosome 8q24.…”
Section: Potential Genomic Alterations In Cholesteatomasmentioning
confidence: 99%
“…The c‐myc gene is located on chromosome 8q24. Previous studies have shown that the aneuploidy of chromosome 8 and copy‐number alterations of the c‐myc gene are associated with the proliferative and aggressive nature of cholesteatomas . Aneusomy of chromosomes 7 and 17 has also been suggested to play a crucial role in cholesteatoma growth and bone destruction …”
Section: Potential Genomic Alterations In Cholesteatomasmentioning
confidence: 99%
“…The study was conducted in compliance with the principles of the Declaration of Helsinki (1964). As it was described previously 26 patients with acquired cholesteatoma comprised of 11 females and 15 males were recruited in the study [ 18 ]. The age of cholesteatoma patients ranged between 4 and 65 years (average: 23.4 years).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of cholesteatoma in all specimens was confirmed by histopathological examination. Demographic data and a brief clinical history including the age, gender of the patients and surgical parameters of cholesteatoma were described in [ 18 ]. In addition to the 26 cholesteatoma samples, 5 control skin samples from the retroauricular region of healthy individuals were also obtained.…”
Section: Methodsmentioning
confidence: 99%